Application of Rebt Techniques to Reduce Bullying Behavior Among Students at SMP X Gresik - Ziadatur Rif'ah; Prianggi Amelasasih (Jurnal Psikologi, 2025)
This study aims to examine the effectiveness of Rational Emotive Behavior Therapy (REBT) in reducing bullying behavior among eighth-grade students at SMP X Gresik who were identified as perpetrators. The research employed a qualitative case study design involving one student selected through purposive sampling based on reports from guidance and counseling teachers and classroom observations. Data were collected through non-participatory observation, in-depth interviews with counseling teachers, homeroom teachers, and parents, as well as documentation of counseling records. The intervention consisted of six individual counseling sessions using REBT techniques, including identification of irrational beliefs, cognitive disputation, reframing, and imaginal disputation. Data analysis was conducted using qualitative descriptive analysis through data reduction, data display, and conclusion drawing. The results indicate significant improvements in the subject’s cognitive, emotional, and behavioral functioning following the intervention. Irrational beliefs related to aggression and dominance were successfully challenged and replaced with more rational thinking patterns. Emotionally, the subject demonstrated improved self-regulation and reduced impulsive anger responses. Behaviorally, bullying incidents—including verbal harassment, social exclusion, and mild physical aggression—decreased progressively and ceased entirely by the end of the intervention. Additional positive outcomes included increased empathy, cooperative peer interactions, voluntary apologies, and consistent behavioral improvements across both school and home environments. These findings demonstrate that REBT is effective in reducing bullying behavior and can be applied as an evidence-based intervention within school guidance and counseling services.